Análisis de las tecnologías 5G como soporte en las telecomunicaciones en el territorio provincial de Los Ríos. - Verdezoto Cando, Washington Emilio (2022)
The society that is in a constant technological growth, people have witnessed how telecommunications technology radically transforms society therefore this research determines how the implementation of 5G would benefit it. The 5G technology is a complete revolution in design, its many applications and functions, therefore this research proposal aims to analyze it, review its advantages and disadvantages, learn about its operation when providing telecommunication service, expose the reference points involved in this process of providing the 5G and analyze the implementation of this technology in Los Rios. In this way, this case study describes everything you need to know about 5G technology and its implementation in the province of Los Ríos, all its applications and the benefits it will bring to society. It is essential to learn and update in this society of constant change for the reason that over the years these technologies will be able to solve many problems and inconveniences in an effective and simple way.